Legal Protection Against the Police in Applying Force Means During Demonstrations Which Are Ongoing Anarchy - Mogadi, Rahmat Bayu Praditama; Michael, Tomy (International Journal of Social Sciences and Humanities, 2024)
The police are an institution responsible for carrying out law enforcement and protecting the community. In carrying out their security duties during demonstrations, many of them became victims of anarchy. The issue of legal protection for demonstrators has been widely discussed in previous studies, while there is still very little research on forms of protection for police when faced with demonstrations. The aim of this research is to find out what kind of protection is given to the police when implementing coercive measures against demonstrations that are taking place in anarchy. The type of research used is normative and the approach used is a statutory approach and a conceptual approach. So the results of this research can be concluded that forms of legal protection can be provided in the form of consultations and assistance at trials, legal regulations and state obligations can be developed for demonstrations that result in fatalities from the police as well as clear law enforcement instructions for the authorities. to ensure legal protection.